CSC794: Adaptive Semantic Web / College of Computing, Informatics and Mathematics - UiTM, College of Computing, Informatics and Mathematics (Universiti Teknologi MARA (UiTM), 2017)
This course aims to introduce a wide range of methods and techniques that are currently used and researched in the semantic Web. Investigation on the next generation of adaptive Web for more effective, intelligent and supporting applications will also be revealed and explored. Upon completing this course, students should be able to understand ontology for semantic groundwork, fundamentals issues in semantic, automatic classification, modelling technologies and also adaptation technologies with emphasis on semantic Web.